Enhancing Soil Stability through Innovative Microbial-Induced Calcium Carbonate Techniques with Sustainable Ingredient - Samer Rababah; Ahmad Alawneh; Borhan A. Albiss; Hussien H. Aldeeky; Eman J. Bani Ismaeel; Sawsan Mutlaq (Civil Engineering Journal, 2024)
Expansive soil poses significant challenges for civil engineers, leading to structural damage, particularly in lightly loaded structures. This study employs an innovative and sustainable recipe to stabilize highly expansive soil using the Microbial-Induced Calcium Carbonate Precipitation (MICP) technique by substituting conventional ingredients with olive mill wastewater and hydrated lime. A series of laboratory tests were performed to evaluate the improvement in Atterberg's limits, Free Swell, Unconfined Compressive Strength (UCS), and pH, in addition to a series of qualitative measurements, including X-ray diffraction (XRD), Scanning Electron Microscopy (SEM), Optical Microscopic Images, and bacteria growth rate. Different mellowing periods and different cementation concentrations were used. The proposed recipe results showed a 50% reduction in the soil's free swell value. The UCS of the treated soil using the proposed recipe was eight times that of the untreated soil and twice that of the soil treated with the traditional recipe. The SEM images showed flocculation and aggregation in the soil particles, with the voids becoming smaller and filled with calcium carbonate (CaCO3). The XRD results showed the formation of new CaCO3particles. The optimized recipe demonstrated remarkable enhancement improvement and significant changes in soil physical properties and microstructure. Doi: 10.28991/CEJ-2024-010-08-08 Full Text: PDF